Synthesis of highly siliceous ZSM-5 using diaminoalkanes and their application for the conversion of methanol to light olefins - Howden, Michael G (Department of Chemical Engineering, 2016)
The use of organic bases in the synthesis of zeolites can lead to the crystallisation of several completely original structures. Zeolite ZSM-5 is produced using tetrapropylammonium cations. This cationic material can be replaced by amines or diamines, although in this case it becomes more difficult to synthesise the zeolite. ZSM-5 has a three dimensional channel system, having apertures which are slightly larger than 0,5 nm. This means that during reactions, there is a control over the size of the molecules that can enter or exit from the pores of the zeolite: this process is called "shape selective11 catalysis. The conversion of methanol over ZSM-5 proceeds via dehydration to give firstly dimethyl ether and then light olefins. The olefins may subsequently undergo dehydrocyclisation to produce a mixture of light paraffins and aromatics, which are restricted to monocyclics and do not contain more than ten carbon atoms. As a result of these properties, ZSM-5 is an ideal catalyst for several industrial processes. Methanol can be converted directly to synthetic gasoline, or by restricting the conversion, olefins can be obtained. Naturally olefins themselves, as well as alkanes, can be converted to aromatics. An entirely different reaction has been found by using a high pressure and relative low temperature, where olefins can be oligomerised to produce diesel.